Comparison of health promotion through lecture method and audiovisual media on the level of knowledge of students regarding Tuberculosis in Soppeng Regency 2024 - Kas, Sri Rezkiani; Darlis, Idhar (Sekolah Tinggi Ilmu Kesehatan Harapan Ibu Jambi, 2024)
Background: Tuberculosis is still one of the leading causes of morbidity and mortality in the world. In Indonesia, every 30 seconds one person is infected with tuberculosis and an average of 13 people die every hour. However, TB sufferers still face challenges in getting treatment and care. Important risk factors in the epidemiology of pulmonary tuberculosis are socioeconomic status, low income, population density, high unemployment, lack of funds for health services, and low knowledge of TB. There are 3 strategies in health promotion, namely empowerment, atmosphere building, and advocacy. This study aims to see the effect of lecture methods and audiovisual media on the level of knowledge of students about TB. Method: The type of research used is quantitative research using a quasi-experimental design. Results: The students' knowledge regarding TB disease was found to be superior to the control group (audiovisual media) compared to the intervention group (lecture method). Conclusion: Based on research on the comparison between lecture methods and audiovisual media in health promotion regarding TB disease, it was found that audiovisual media is more effective in increasing the level of knowledge of students compared to lecture methods.